Experimental Electronic Literature from the Souths: A Political Contribution to Critical and Creative Digital Humanities - Kozak, Claudia (2021)
This essay aims to evaluate the potential of experimental e-lit to build decolonial critical paths within global digital humanities. In the introduction of the “Electronic Literature [Frame]works for the Creative Digital Humanities” gathering, Alex Saum-Pascual and Scott Rettberg state that the notion of creative digital humanities they work with–that goes hand in hand with critical digital humanities–not only considers e-lit as a creative field of digital humanities, but also “redeploy(s) creative practice critically to address the increasing instrumentalization of the Digital Humanities” (2). In synch with their statement, but stressing the notion of critical and creative digital humanities from a perspective framed by the Epistemologies of the South (Sousa Santos) and decolonial thinking (Mignolo), I propose entangled conceptualizations and possible lines of analysis to give shape to what I would like to call “decolonial e-lit/dh”. On the one hand, this may be an option to debate the usual ways of understanding e-lit global history, theory, critique and practice. On the other hand, it may also contest digital humanities considered primarily in terms of a set of global tools for dealing with cultural entities in the field of humanities. The latter comprises an instrumental bias which relies on an instrumental approach to technology as allegedly neutral, with few or none relation to broader socio-technical dimensions. Despite that a merely instrumental approach to digital humanities has already been discussed by many authors (among others, Berry 2012, Fioromonte 2012, Liu 2012), it still prevails.